Deposit withdrawals from distressed banks: Client relationships matter - Brown, Martin; Guin, Benjamin; Morkoetter, Stefan (Journal of Financial Stability, 2020)
We study retail deposit withdrawals from commercial banks that were differentially exposed to distress during the 2007–2009 financial crisis. We show that the propensity of clients to withdraw deposits increases with the severity of bank distress. However, an exclusive pre-crisis bank-client relationship eliminates withdrawal risk. The mechanism through which strong bank-client relationships mitigate withdrawal risk relates to the transaction costs of switching accounts rather than informational rents or differentiated services. Our findings provide empirical support to the Basel III liquidity regulations that emphasize the role of well-established client relationships for the stability of bank funding.